Establishment of a method for detecting complement C3d-sensitized platelets - LI Hongyang; YU Hongmei; WANG Changmin; LIU Tiemei (Zhongguo shuxue zazhi)
[Objective] To establish a detection method for complement C3d-sensitized platelets. [Methods] Parallel detection of the same platelet sample under conditions of complement C3d sensitization and non-sensitization was conducted using microcolumn gel immunoagglutination inhibition assay technology. The supernatant obtained after the reaction between anti-C3d monoclonal antibodies and platelet samples was then reacted with C3d-sensitized red blood cells to observe whether agglutination occurs. Subsequently, this method was used to test samples from 22 clinical patients to determine whether their platelets were sensitized by complement C3d. [Results] The same platelet sample, after being sensitized with complement C3d, showed negative or weakened aggregation, which was determined as a positive result, whereas platelets that were not sensitized with complement C3d exhibited aggregation, which was determined as a negative result. A total of 22 clinical patient samples were tested, of which 16 were negative and 6 were positive. [Conclusion] A microcolumn gel immunoagglutination inhibition test was established to detect whether platelets are sensitized by complement C3d, which aids in the auxiliary diagnosis of complement-related immune diseases involving platelets.